Autism spectrum disorders among adolescents and adults and comparison with schizophrenia - Küçük, Aylin; Maner, Fulya; Ceylan, Mehmet Emin (The European Research Journal, 2019)
Objectives: Autism Spectrum Disorders (ASD) may be commonly misdiagnosed as schizophrenia due to common symptoms and accompanying psychotic manifestations in both adolescence and adulthood. The purpose of this study is to examine and compare the autistic symptoms and positive and negative symptoms of schizophrenia in cases diagnosed as Autism Spectrum Disorder. Methods: Twenty-one patients between ages of 16-36 who have admitted to outpatient clinic have previously been diagnosed as autism spectrum disorders (autistic disorder, Asperger Syndrome, pervasive development disorder not otherwise specified) according to DSM-IV diagnosis criteria, have an IQ of 50 or above, have been included in the study. Control group have been composed of 21 patients between ages of 21-39 who have been diagnosed as schizophrenia according to DSM-IV diagnosis criteria and have an IQ of 50 or above. Psychiatric assessment has been made with Childhood Autism Rating Scale (CARS), Scale for the Assessment of Positive Symptoms (SAPS), Scale for the Assessment of Negative Symptoms (SANS), SCID-I and WAIS. Results: The negative symptoms of ASD are found to be higher than schizophrenia cases where as the positive symptoms of schizophrenia cases are found to be higher than ASD cases. Twenty percent (n = 4) of OSB cases do not meet autism symptoms while none of the schizophrenia cases meet autism symptoms. In one case of the ASD group, additional schizophrenia diagnosis was present. Conclusions: In this study, it has been found that negative symptoms of schizophrenia are widely observed in adolescent and adult patients followed with ASD diagnosis. Consequently, autism spectrum disorders are manifested common symptoms with schizophrenia in adolescence and adulthood.